Social Integration and Attitudes towards the Integration of Immigrants in Relation to Witnessing Domestic Aggression - Ingrida Grigaityte; Karin Osterman; Kaj Bjorkqvist (Journal of Educational, Health and Community Psychology, 2021)
The association between witnessing domestic aggression and respondents' level of social integration and their proactive attitudes towards the integration of immigrants was assessed with a questionnaire in a sample of the Swedish-speaking minority in Ostrobothnia, Western Finland (n = 298; 208 females and 90 males). The age span was between 16 and 90 years with a mean age of 31.6 years (SD = 13.5). Respondents scoring higher than average on witnessing domestic aggression scored lower than others on the following scales measuring social integration: Access to Social Benefits, Positive Social Relations, and Trust in the Finnish Judiciary System. They also scored lower than others on the following scales measuring proactive attitudes towards the integration of immigrants: (the need for making) Cultural Efforts, Structural Efforts, and Openness to Diversity. They also tended to have a lower level of education than other respondents. The implications of the findings are discussed.Â